Study of the effect of changing the percentage of germanium affinity for pure silica on the bending coefficient of physical dissipation. - Dayoub, Nazir (Latakia University Journal -Basic Sciences Series, 2019)
We know that pure optical velocity is directly related to the optical fiber refraction hypothesis, and that the refractive index changes with the wavelength change and thus the wave velocity changes with the change in length. The concept of dissipation reflects the process of changing the wavelength with the change of speed and relates to several factors including the properties of the material used, which is called physical dissipation. In this paper we studied the effect of the change in the ratio of the GeO2 element to the pure silica on the change of the refractive index with the wavelength constant, As well as the coefficient of physical dissipation of silica similar to the previous element and the same proportions of infection